1995
DOI: 10.1007/bf00191804
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the elastin gene in 60 patients with clinical diagnosis of Williams syndrome

Abstract: Williams syndrome (WS) is caused by deletion of the elastin (ELN) gene. We have analyzed an intragenic restriction fragment length polymorphism (RFLP) and the gene dosage of ELN using a new probe (FP4) in a series of 60 sporadic patients with a clinical diagnosis of WS. Deletion of the ELN gene was shown in 54 cases, while clinical revaluation of the 6 patients without the deletion did not confirm the diagnosis of WS. These results support the genetic homogeneity of WS, and the high accuracy of ELN molecular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 13 publications
1
24
1
1
Order By: Relevance
“…Participants lived with their families who gave their informed consent. The Williams--Beuren syndrome diagnoses had been established by pediatricians and confirmed by molecular analyses (homozygous deletion of the elastin gene, 7q11.2, Mari et al, 1995). Intellectual levels were obtained from psychological records of these patients (mainly on the Stanford-Binet and Wechsler scales).…”
Section: Participantsmentioning
confidence: 99%
“…Participants lived with their families who gave their informed consent. The Williams--Beuren syndrome diagnoses had been established by pediatricians and confirmed by molecular analyses (homozygous deletion of the elastin gene, 7q11.2, Mari et al, 1995). Intellectual levels were obtained from psychological records of these patients (mainly on the Stanford-Binet and Wechsler scales).…”
Section: Participantsmentioning
confidence: 99%
“…After establishment of linkage between SVAS and the elastin gene (ELN) on chromosome 7 (Ewart et al 1993a), four familial and five sporadic cases of WS were described, with deletions encompassing the ELN at 7q11.23 (Ewart et al 1993b). The usefulness of ELN molecular analysis has since been confirmed in several studies of WS patients comprising a total of 368 patients (Kotzot et al 1995;Lowery et al 1995;Mari et al 1995;Nickerson et al 1995).…”
Section: Introductionmentioning
confidence: 95%
“…WS is generally sporadic with an incidence of 1/20,000-1/50,000 live births, although familial cases have been reported with appar- [Curren et al, 1993;Morris et al, 1993b;Ewart et al, 1994;Olson et al, 1995;Li et al, 1997;Tassabehji et al, 1997]. Further investigations of SVAS and WS have shown that hemizygosity at the elastin locus occurs in most WS patients Keating, 1994;Borg et al, 1995;Kotzot et al, 1995;Nickerson et al, 1995;Lowery et al, 1995;Mari et al, 1995]. Elastin haploinsufficiency provides an explanation for some of the anomalies found in WS, including SVAS, and a hoarse voice and rapidly aged-appearing skin, which may occur in part because elastin is required for the normal ultrastructure in the vocal ligaments and the skin.…”
mentioning
confidence: 94%